Enhancing Internet of Things conceptual, practical and programming learning skills - Santos, Matias R. P. dos; Callado, Arthur de Castro; Laurindo, Luis Eduardo C. (Anais do Workshop sobre Educação em Computação (WEI); 2024: Anais do XXXII Workshop sobre Educação em Computação, 2024)
The Internet of Things (IoT) is a computational paradigm that facilitates the interconnection of intelligent objects to the Internet, enabling interaction, operational efficiency, and communication. Moreover, it allows the collection of various environmental data, which can be processed to develop applications for diverse uses, such as e-health and smart agriculture. Therefore, due to the significant technological advancements and their continuous development and improvement, it is crucial to utilize alternative platforms for teaching and learning these technologies. These platforms should aim to enhance understanding and facilitate application development within these ecosystems. Utilizing tools for simulating or emulating IoT environments can facilitate practice, provide hands-on experience, reduce costs, and enhance agility in creating teaching proposals. This paper analyzes tools and platforms that aid in learning and developing IoT concepts and networks. Specifically, it discusses Internet of Things concepts and tools for simulating or emulating widely used environments.